Thalassemia in Sri Lanka: a progress report. - Premawardhena, A; De Silva, S; Arambepola, M; Olivieri, N; Merson, L; Muraco, J; Allen, A; Fisher, C; Peto, T; Vichinsky, E; Weatherall, D (2004)
The thalassemias pose an increasing burden for health-care services in many Asian countries. In order to conserve rare resources, it is essential to determine the reasons for the remarkable phenotypic heterogeneity and natural history of these disorders so that the most cost-effective methods for their control and management can be established. A long-term observational study of patients with different forms of thalassemia in Sri Lanka suggests that in addition to the well-defined primary, secondary and tertiary genetic modifiers, environmental factors, particularly malaria, and variation in the ability to adapt to the profound anaemia which characterizes these conditions, may play a significant role in determining their clinical severity. These findings may have important implications for the control and management of thalassemia in Asian populations.